Kajian Harmonisa Pada Pemakaian Tenaga Listrik Gedung STT-PLN Jakarta - Tony Koerniawan; Aas Wasri Hasanah (KILAT, 2019)
Harmonic is produced by non-linear loads in electrical system. The using of non-linear loads in utility system increaces harmonics in the result sinusoidal waveform of current and voltage can not occur. A harmonic filter is expected to decrease harmonic in STT-PLN electricity consumption which have current and voltage of harmonic distortion on the threeth. Therefore we need a filter that can reduce the impact of harmonics that occur so as to provide better power quality.